(untitled) (International Journal of Studies in Nursing, 2018)
Substance use is a major health concern among women, as approximately 15.8 million have used an illicit drug in the past year. Another 4.3 million have misused prescription drugs. Men are more likely to engage in illicit drug use than women, however, the gender gap is narrowing. The consequences of substance abuse not only negatively impact women, but may affect the cognitive and physical abilities of their children. For methodology, electronic searches were conducted using scholarly databases with various combinations of keywords related to women, substance abuse, addiction, nursing care, pregnancy, and gender difference. Research trends indicate that women often present with gender-specific needs, including physiologically, socially, and economically. This article gives an overview of some gender differences between men and women and how they influence treatment and outcomes for women. It also discusses special considerations for nurses caring for women with substance use disorders.